Membrane Estrogen Receptors Acting in the Central Nervous System - Micevych, Paul E.; Mermelstein, Paul G. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2009)
Estrogens, like many other hormones, affect both the central and peripheral nervous system. Initially identified as initiator of gene expression through activation of transcription factors that directly bind DNA, estrogens have also been shown to alter intracellular signaling via membrane surface activation of G proteins. The idea that estrogens can rapidly signal via membrane receptors is well accepted, but the exact nature of the membrane estrogen receptor(s) (mER) remains controversial. Several putative mERs have been described, including ER-X, an STX-binding protein and GPR30. That said, the majority of estrogenic effects initiated at the cell surface appear to be due to membrane trafficking of the classical estrogen receptors, estrogen receptor- α (ERα) and estrogen receptor-β (ERβ). This paper will review the evidence that rapid estrogen actions through different putative mERs mediate sexual receptivity and the luteinizing hormone (LH) surge. Since a large number of rapid responses appear to be due to ERα and ERβ, the same proteins that regulate gene expression within the nucleus, we will focus on how the classical ERα and ERβ are trafficked to the membrane and initiate cell signaling. As ERα and ERβ are themselves not GPCRs, to activate G proteins they interact with metabotropic glutamate receptors (mGluRs) that function as intermediaries, to transduce the ligand activation of membrane ERα and ERβ spare into a cellular response. This ER/mGluR hypothesis provides a mechanism to explain the wide-range of rapid estrogen actions in the brain.
Keywords: estrous cycle